A past before a blueprint: Malaysia's challenges in English Language teaching - Hall, Stephen J. * (IELTS, 2015)
Malaysia has invested heavily to develop education and language competencies for national and transnational needs, including English for international communication. Any attempt to meet English language needs of ASEAN partners could benefit from lessons from the past and a focus on productive multilingualism, especially in a linguistically diverse nation There is a history of addressing the urban and rural divide with various projects to build English language skills for a knowledge-based economy, yet there may not always be synthesis from these initiatives when policies change. The most recent aspirations in the form of eleven shifts in the Malaysian 2013-2025 Education Blueprint are presented as transformation and they address many possibilities. Challenges in moving Malaysia up from its PISA ratings for literacy and reading skills are also made complex with a multilingual educational system and questioning of the position of English vis-a-vis the national language. This chapter will argue that capacity building for ASEAN integration, through developing English for effective international communication, depends on long-term strategies built on recognizing linguistic complexity in classrooms. An in-service teacher education project will be used as a case study of the challenges in aligning top-down planning with classroom-based development.